Modifikasi Protokol Routing DSDV Menggunakan Algoritma Dynamic-power transmission untuk Mengurangi Interferensi Sinyal dalam Pengiriman Data Berdasarkan Tingkat Kepadatan Node di Jaringan MANET: Modification of DSDV Routing Protocol Using Dynamic-power transmission Algorithm to Reduce Signal Interference in Data Delivery Based on Node Density Level in MANET - Desyra Ardiani; Hidayat Jatmika, Andy; Ariyan Zubaidi (Journal of Computer Science and Informatics Engineering (J-Cosine), 2023)
Mobile Ad-Hoc Network (MANET) is a decentralized collection of nodes that exchange information temporarily via wireless transmission. When nodes communicate, all nodes in the communication range will be affected by signal interference from other nodes. The problem that arises due to this signal interference is that it will affect or interfere with the signal transmitted to the receiver, resulting in a decrease in network performance which will impact the quality of service (QoS). To overcome the problem of signal interference, use interference management. This study applies the Dynamic-Power Transmission (DPT) algorithm to the Destination Sequence Distance Vector (DSDV) routing protocol framework. DPT-DSDV will adjust the communication range automatically based on the node density level. When a node sends data packets to neighbouring nodes, the communication range will be adjusted automatically based on the selected level. The performance of DPT-DSDV will be compared with standard DSDV and standard AODV by looking at performance based on three parameters, namely throughput, packet delivery ratio (PDR), and end-to-end delay. Based on the results of research trials, applying the dynamic-power transmission algorithm can improve the performance of the standard DSDV routing protocol. Throughput results on DPT-DSDV increased by 0.90%. The packet delivery ratio (PDR) increased by 0.50%, and end-to-end delay decreased by 2.80%. Key words: MANET, Interference, Quality of Service, Routing, DSDV, Dynamic-Power Transmission.